Kaempferol alleviates rheumatoid arthritis through pyroptosis based on bioinformatics analysis and experimental validation - Yi Ling; Nina Ren; Yuzheng Yang; Hui Xu; Hong Xiong; Qiuyi Wang; Daomin Lu; Xueming Yao; Wukai Ma (Scientific Reports)
Abstract Kaempferol has an anti-inflammatory effect on rheumatoid arthritis (RA), but the mechanism by which inflammatory reactions are relieved via pyroptosis is still unclear. In the present study, The bioinformatics technology was used to analyze the relationship between pyroptosis the hub genes and the downstream cytokines in RA from three the Gene Expression Omnibus (GSE12021, GSE1919 and GSE29746). Molecular docking analysis of kaempferol and caspase1 (CASP1) was executed with Autodock tools. RA fibroblast-like synoviocytes (RA-FLS) was used to explore the anti-inflammatory effects of kaempferol on RA via pyroptosis. Thirty-seven differentially expressed genes (DEGs) were identified from the three datasets, and the enrichment analysis was focused mainly on the chemokine signaling pathway. The difference in immune cell infiltration was focused on CD4 T cells, CD8 T cells, M1 macrophages, and M2 macrophages. The expression of CASP1 and caspase3 (CASP3) was higher in the RA group. CASP1 and CASP3 were positively correlated with cytokines interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α). Moreover, molecular docking revealed that kaempferol strongly interacts with CASP1. Kaempferol inhibited the proliferation and migration of RA-FLS in vitro. The expression of CASP1, CASP3, caspase5 (CASP4), caspase5 (CASP5), gasdermin D (GSDMD), N-terminal domain of gasdermin D (GSDMDNT), IL-1β, and cytokines interleukin-18 (IL-18) were significantly affected by kaempferol. Kaempferol alleviated RA-FLS membrane disruption, and it blocked CASP1 to alleviate RA via pyroptosis. The present study demonstrated that kaempferol binds to CASP1 and affects pyroptosis in RA, thereby serving as an anti-immunotherapy strategy.